Dispositional resilience predicted the perceived stress experienced by psychotherapists during the COVID-19 outbreak - Tavel, Peter; Trnka, Radek; Furstova, Jana; Kascakova, Natalia; Kuska, Martin; Meier, Zdenek (Psychological services, 2022)
The coronavirus disease (COVID-19) pandemic elicited huge stress responses in most world populations, and at this time psychotherapy is an important protective service against this stress. However, a somewhat neglected question is: How stressful was the COVID-19 outbreak for psychotherapists themselves? The main aim of the present study was to investigate whether dispositional resilience predicted the perceived stress reported by psychotherapists during the COVID-19 outbreak. A total of 338 psychotherapists organized within the national psychotherapy associations of three European countries (Czech Republic, Germany, and Slovakia) were included in this online study (mean age 46.7, 77.8% female, 22.2% male). The participants were administered the Perceived Stress Scale (PSS-10) and the Connor-Davidson Resilience Scale (CD-RISC). For the data analysis, nonparametric ANOVA and two-level (mixed-effect) linear regression models were used. Dispositional resilience significantly predicted the perceived stress reported by psychotherapists during the COVID-19 outbreak. Higher dispositional resilience significantly reduced the level of perceived stress among psychotherapists (adjusted β = -0.47, p < .001). Those with moderate resilience (between mean ± SD values) had a lower perceived stress score than those with low resilience (<mean -SD value) by an average of 3.5. Psychotherapists in the high resilience group (>mean + SD value) had a lower perceived stress score than the low resilience group by an average of 6.5. The results of this study imply that the involvement of psychotherapists in resilience supportive training may reduce their vulnerability to stress. (PsycInfo Database Record (c) 2022 APA, all rights reserved).
Keywords: psychoterapie; psychický stres; psychická odolnost; Psychotherapists; Male; Pandemics; Psychotherapy; lidé; Female; mužské pohlaví; ženské pohlaví; Resilience, Psychological; pandemie; Humans; Stress, Psychological; psychoterapeuti; COVID-19